(untitled) (Medical Forum Monthly, 2024)
Objective: This study was carried out to know the frequency and magnitude of different breast diseases including all the benign, malignant and inflammatory lesions in the local population of Bahawalpur in south Punjab, Pakistan. Study Design: Descriptive cross-sectional study design. Place and Duration of Study: This study was conducted at the Department of Pathology, Quaid-e-Azam Medical College/Bahawal Victoria Hospital, Bahawalpur, Pakistan from January 2004 to December 2006. Materials and Methods: A retrospective data analysis of breast biopsies and mastectomies based upon histopathology. Results: Histopathological analysis revealed that out 166 cases, 50% were benign, 37.34 % were malignant and 12.65 % were inflammatory lesions; mean age of diagnosis was 33.2, 49 and 31.75 years for these lesions respectively. Of all the breast lesions, fibroadenoma was the most common 39.15 % (65 patients), followed by invasive ductal carcinoma 33.73 % (56 patients). Non proliferative breast changes (fibrocystic changes 4.81 % and adenosis 3.01%) ranked third with 13 patients, while chronic mastitis and breast abscess were the fourth (5.42 %) and fifth (3.61%) common diagnoses respectively. Mean age of diagnosis for fibroadenoma and invasive ductal carcinoma was 21 and 48 years respectively. Conclusion: Fibroadenoma was the most common histopathological diagnosis while invasive ductal carcinoma was the most common malignancy of breast as well as the second most common diagnosis. Mean age of diagnosis for breast carcinoma was 49 years.